(untitled) (Al-Aasar, 2024)
Cultural narratives and historical memory play pivotal roles in shaping the collective identity of societies. These narratives, which stem from the historical experiences, traditions, and shared heritage of communities, contribute to the formation of national and local identities in modern societies. The ongoing interaction between heritage preservation, cultural narratives, and evolving social dynamics is examined in this article to understand their influence on contemporary societies, particularly in Pakistan. By exploring the ways in which historical memory is preserved, transmitted, and reinterpreted, this study highlights how these processes impact cultural cohesion and identity in a rapidly changing world. The implications of this research offer insights into the significance of heritage in fostering a sense of belonging and its role in shaping modern societal transformations.